The relationships between North Atlantic SST and extratropical cyclones - Valkonen, Elina (Helsingfors universitet, 2016)
Extratropical cyclones can have major impacts on our daily lives, and therefore any drastic changes in their frequency or characteristics, such as intensity or radius, can have a great impact on society. Extratropical cyclones do not only affect everyday weather, but can cause extreme weather events from floods to drought and are also largely in charge of the equator-to-pole energy, momentum and moisture transports. In the recent years, there has been an increasing amount of both numerical and observational studies to suggest a poleward shift of the storm tracks with the warming climate. This shift could have major impacts all around the world through weather extremes and climatic effects. Even though a vast amount of research has been done, a definite answer, as to how will the location of the storm track change in the near future, remains unanswered. This study aims to answer the question of how has the location of the North Atlantic storm track changed with the changing surface temperatures, with the focus on the effects of the sea surface temperatures. In this study the CFSR (Climate Forecast System Reanalysis) reanalysis products from 1979-2014 was analysed. The cyclones were tracked based on the Laplacian of the surface pressure using the Melbourne University Cyclone Tracking Algorithm. First the differences between 1979-1988 and 2005-2014 for both surface temperature and extratropical cyclone track density, a measure of the storm track, were calculated and after that the correlation between ST and both track density and North Atlantic Oscillation (NAO) index were calculated for the whole study period, 1979-2014. All the above mentioned calculations were done separately for four seasons (DJF, MAM, JJA, SON) and also for two six month periods (Oct-Feb, Mar-Sep). The results show that the North Atlantic has warmed significantly, with the strongest warming taking place in the Arctic in winter. There were also clear changes in the cyclone frequecy, but these changes were not as spatially coherent as the ...